Pelaksanaan Manajemen Strategi dalam Peningkatan Mutu Pendidikan Agama Islam di SDIT Izzatul Islam Kecamatan Cibarusah Kabupaten Bekasi - Fathin Kusumardani; Achmad Junaedi Sitika; Debibik Nabilatul Fauziah (FONDATIA, 2022)
This research is motivated by strategic management in improving the quality of Islamic religious education in elementary schools which is still low. Schools in order to provide quality education, educational management strategies must be formulated thoroughly. To realize the implementation of strategic management in improving the quality of Islamic religious education in Izzatul Islam, a leader and manager of educational institutions is needed. The principal as a leader in educational institutions has a very dominant role in improving the quality of education so that it is of high quality. The focus of this study is to analyze how the implementation of strategic management in improving the quality of Islamic religious education at SDIT Izzatul Islam. This study aims to determine the implementation of strategic management in improving the quality of Islamic religious education at SDIT Izzatul Islam. This research is a descriptive qualitative research. The location of the research was carried out at SDIT Izzatul Islam, Cibarusah District, Bekasi Regency. Based on the results of research at SDIT Izzatul Islam, it shows that strategic management in improving the quality of Islamic religious education goes through three processes, namely (1) formulation, by formulating the school's vision and mission, (2) implementation, by implementing school policies and motivating educators and educators. education, (3) evaluation and control by covering activities such as planning, implementation process, supervision to the results of activities.